Proceedings of the Ocean Drilling Program 1990
DOI: 10.2973/odp.proc.sr.113.167.1990
|View full text |Cite
|
Sign up to set email alerts
|

The Diagenetic Factors Controlling the Dissolved Organic Carbon (DOC) in Pore Water from Deep Sea Sediments (ODP Leg 113|Weddell Sea)

Abstract: Dissolved organic carbon (DOC) was determined in pore water extracted from pelagic and hemipelagic sediments re covered during Leg 113. DOC concentration varied between 1.82 and 13.6 mg C/L which is one to two orders of magni tude less than previously reported for hemipelagic sediments. It is argued that this difference is related to differences in the intensity of degradation of organic matter. As a first approximation it is found that in reducing sediments, the level of DOC is proportional to the intensity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…One possible explanation for the higher DFAA at Sites 689 and 690 is reduced microbiological activity because small decrease in sulfate in interstitial waters results from low organic carbon content. It is consistent with low DOC concentrations at Sites 689 and 690 (Egeberg and Abdullah, 1990). Smear slide observations indicated that the major constituents of the sediments from Sites 689 and 690 were biogenic material.…”
Section: General Characteristics Of Dcaa In Interstitial Waterssupporting
confidence: 64%
See 2 more Smart Citations
“…One possible explanation for the higher DFAA at Sites 689 and 690 is reduced microbiological activity because small decrease in sulfate in interstitial waters results from low organic carbon content. It is consistent with low DOC concentrations at Sites 689 and 690 (Egeberg and Abdullah, 1990). Smear slide observations indicated that the major constituents of the sediments from Sites 689 and 690 were biogenic material.…”
Section: General Characteristics Of Dcaa In Interstitial Waterssupporting
confidence: 64%
“…Carbonate content was very low (0-3.9 wt.%) in Unit 1, variable in Unit 2A (0.8-91.3 wt.%) and high in Units 2B and 3 (75.5-98.1 wt.%). Organic carbon content was low throughout the hole with the mean value 0.11 wt.% (Egeberg and Abdullah, 1990).…”
Section: Summary Of the Geological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfate profiles in deep-sea sediments are usually concave downward, although linear profiles like those observed at Site 991 are not uncommon (e.g., Egeberg and Abdullah, 1990;Borowski et al, in press). Linear SO 4 2~ profiles can be attributed to extensive SO 4 2~ depletion in a restricted subsurface interval accompanied by downward SO 4 2 " diffusion.…”
Section: Factors Controlling Sulfate Depletionmentioning
confidence: 99%
“…In contrast to the numerous DOC profiles published from surficial (<1 m) marine sediments (e.g., Krom and Sholkovitz, 1977;Burdige et al, 1992Burdige et al, , 1999Alperin et al, 1994Alperin et al, , 1999Burdige and Homstead, 1994;Burdige and Zheng, 1998;Burdige, 2002Burdige, , 2006, only a few studies have examined pore water DOC concentrations within profiles extending to greater sediment depths (Michaelis et al, 1982;Egeberg and Abdullah, 1990;Seifert et al, 1990;Wefer et al, 1998;Simoneit and Sparrow, 2002;Heuer et al, 2009). Although the DOC concentrations within surficial sediments generally increase exponentially with increasing depth from the seawater/sediment interface until reaching an asymptotic maximum, DOC concentrations within deep sediment pore water generally do not demonstrate such systematic variation with depth.…”
Section: Introductionmentioning
confidence: 99%